Le latino-américanisme français en perspective - Mona Huerta (Caravelle)
This article aims to show the evolution of the often contrasting cultural and scientific ties that France has with Latin America, emphasizing in particular the elements of their revival after the Second World War and their transformations in the early twenty-first century. If art and culture have been the cornerstone of these relationships since the late nineteenth century, the region was for the French researchers a fruitful laboratory that inspired the construction of Latin American Studies in France. Back on a story to feed the reflection on the changing Area Studies, in times of globalization.